Corporate governance at Martha Stewart Living Omnimedia : not "a good thing" - Shein, James B., 1942- (SAGE knowledge. Cases., 2016)
The case opens with Martha Stewart's 2005 release from prison following her conviction for obstructing an insider-trading investigation of her 2001 sale of personal stock. The scandal dealt a crippling blow to the powerful Martha Stewart brand and drove results at her namesake company, Martha Stewart Living Omnimedia (MSO), deep into the red. But as owner of more than 90 percent of MSO's voting shares, Stewart continued to control the company throughout the scandal.